Computed Tomography Guided Fine Needle Aspiration Cytology of Lung Lesions: A Study of 162 Cases - Ahmed, Syed; Ahamad, M Shahab Uddin (Journal of Chittagong Medical College Teachers’ Association, 2010)
Key words: CT; FNAC; Lung DOI: 10.3329/jcmcta.v20i1.4936 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):50-52